Corporate Control, Portfolio Choice, and the Decline of Banking - GORTON, GARY; ROSEN, RICHARD (Journal of Finance, 1995)
ABSTRACT In the 1980s, U.S. banks became systematically less profitable and riskier as nonbank competition eroded the profitability of banks' traditional activities. Bank failures rose exponentially during this decade. The leading explanation for the persistence of these trends centers on fixed‐rate deposit insurance: the insurance gives bank equityholders an incentive to take on risk when the value of bank charters falls. We propose and test an alternative explanation based on corporate control considerations. We show that managerial entrenchment played a more important role than did the moral hazard associated with deposit insurance in explaining the recent behavior of the banking industry.